THE EFFECTIVENESS OF STRESS MANAGEMENT EDUCATION IN A WAY OF BEHAVIORAL COGNITIVE ON BODY IMAGE AND MARITAL INTIMACY OF WOMEN SUFFERING FROM EVACUATED BREAST CANCER - Oraki, Mohammad; hasannezhad, Nahid; Jahandar, Maryam (International Journal of Psychosocial Rehabilitation, 2020)
The goal of the present study had been the effectiveness of stress management education in a way of behavioral cognitive on body image and marital intimacy of women suffering from evacuated breast cancer. The study method is semi-pilot with pretest-posttest plan and control group. The research's statistical population, includes recently diagnosed women in the first and second stage of evacuated breast cancer who referred to Ayatollah Rouhani hospital in Babol in 2009. This practical study examined 30 people in two groups of test with 15 people and control group with 15 people, randomly. The questionnaires of scare of body image and Bertmann marital intimacy questionnaire were used in pretest and posttest as means for collecting data. The tests were conducted during 10 weeks of stress management education in a way of cognitive. The scores changes of body image and marital intimacy between intervention and control groups in posttest were meaningful. And then in intervention group, a meaningful difference observed between pretest and posttest in body image and marital intimacy variables. The stress management education in cognitive behavioral way impacts on body image and marital intimacy of women who suffer from evacuated breast cancer.